A 23-year bibliometric analysis of the development of global research on hereditary renal carcinoma - Lan, Xiaopeng; Feng, Mei; Lv, Ji; Zhang, Luchen; Hu, Pengcheng; Wang, Yizhen; Zhang, Yanhui; Wang, Shen; Liu, Chunzhao; Liu, Chunlei (Frontiers in Oncology, 2024)
Objectives Medical research continues to be extensively devoted to investigating the pathogenesis and treatment approaches of hereditary renal cancer. By aspect including researchers, institutions, countries, journals, and keywords, we conduct a bibliometric analysis of the literature pertaining to hereditary renal cancer over the last 23 years. Methods From the Web of Science Core Collection, we conducted a search for publications published between January 1, 2000 and November 28, 2023. Reviews and original articles were included. Results A cumulative count of 2,194 publications met the specified criteria for inclusion. The studies of the included articles involved a collective of 2,402 institutions representing 80 countries. Notably, the United States exhibited the highest number of published documents, constituting approximately 45.49% of the total. The preeminent institution in this discipline is the National Cancer Institute (NCI), which maintains a publication volume of 8.98%. In addition to being the most prolific author (125 publications), Linehan WM’s works received the highest number of citations (11,985). In a comprehensive count, 803 journals have published related articles. In the top 10 most recent occurrences were the terms “hereditary leiomyomatosis” and “fumarate hydratase.” Conclusion This is the first bibliometric analysis of the literature on hereditary renal cancer. This article offers a thorough examination of the present status of investigations concerning hereditary renal cancer during the previous 23 years.